Numerical Assessment of the Seismic Performance of a Timber Retrofit Solution for Unreinforced Masonry Buildings. Issue 1 (2nd January 2023) - Damiani, Nicolò; Miglietta, M.; Guerrini, G.; Graziotti, F.
ABSTRACT: This paper presents the results of a numerical study about the effectiveness of a new multi-component timber retrofit solution for unreinforced masonry buildings in seismic regions. The proposed retrofit consists of timber frames fastened to the internal surface of masonry piers, with oriented strand boards eventually nailed to the frames. This technique aims at improving both in-plane and out-of-plane capacities of masonry piers as well as wall-to-diaphragm connections. Numerical models were built and calibrated against experimental data from quasi-static cyclic shear-compression tests on two isolated piers and dynamic shake-table tests on two full-scale buildings, in bare and retrofitted conditions. The building prototype represented the end-unit of a cavity-wall terraced house. A strategy to include the retrofit contribution in equivalent-frame masonry models is proposed. Starting from the calibrated models, two additional strengthening schemes were numerically generated to investigate the influence of increasing retrofit levels on the building performance. For each model, a cloud nonlinear time-history analysis was performed using 250 ground-motion records to derive damage-state fragility functions. The numerical outcomes can assist in the selection of an optimal level of the proposed retrofit solution, balancing structural and economic goals.